Prospects of sustainable photovoltaic powered thermoelectric cooling in zero energy buildings: A review. (10th August 2022) - Chandel, Rahul; Chandel, Shyam Singh; Prasad, Deo; Dwivedi, Ram Prakash
Summary: Thermoelectric module (TEM) is a scalable, reliable, and noise‐free solid‐state device that converts thermal energy into electrical energy and vice‐versa. TEM has been explored for cogeneration, electronics cooling, power production, waste heat harnessing, and air‐conditioning. The potential applications of TEM‐based systems are in the building, for heating, ventilation, and air‐conditioning (HVAC), which represents its significant share in the energy consumption in the building sector. A photovoltaic powered thermoelectric system has even a stronger techno‐economical potential. The main objective of the study is to explore the potential of PV‐powered thermoelectric technology as a distributed air‐conditioning system in buildings. In this study, a comprehensive review on PV‐powered thermoelectric technology is presented in addition to several new design concepts for application in future development of sustainable zero energy building technologies in view of sustainability and global climate change concerns. A novel "STEM‐Wall" concept is also discussed concerning future thermoelectric system designs for buildings. Additionally, the thermal comfort aspect of HVAC systems is critically analyzed by reviewing the standard predicted mean vote and predicted percentage of dissatisfied indices. The research outcome, analysis, and potential of TEM applications for future sustainability and thermal comfort in buildings are presented. Further follow‐up research areas are also identified. Abstract : Due to the solid‐state operation and non‐requirement of refrigerants, photovoltaic (PV)‐thermoelectric technology has inspired interest in the potential application for air‐conditioning of buildings. Global climate change and transition toward zero energy buildings (ZEB) necessitate research into alternative cooling technologies for building application. In this study, a comprehensive review on PV‐powered thermoelectric technology is presented in addition to several new design concepts for application in ZEB including a novel semi‐transparent thermoelectric module wall system. Future research areas are also identified.